Beyond skill scores: exploring sub‐seasonal forecast value through a case‐study of French month‐ahead energy prediction. (3rd August 2020) - Dorrington, Joshua; Finney, Isla; Palmer, Tim; Weisheimer, Antje
Abstract: We quantify the value of sub‐seasonal forecasts for a real‐world prediction problem: the forecasting of French month‐ahead energy demand. Using surface temperature as a predictor, we construct a trading strategy and assess the financial value of using meteorological forecasts, based on actual energy demand and price data. We show that forecasts with lead times greater than two weeks can have value for this application, both on their own and in conjunction with shorter‐range forecasts, especially during boreal winter. We consider a cost/loss framework based on this example, and show that, while it captures the performance of the short‐range forecasts well, it misses the marginal value present in medium‐range forecasts. We also contrast our assessment of forecast value to that given by traditional skill scores, which we show could be misleading if used in isolation. We emphasise the importance of basing assessment of forecast skill on variables actually used by end‐users. Abstract : Sub‐seasonal forecasting aims to extend atmospheric predictability out 3–6 weeks into the future. We quantify the value these forecasts actually provide for a real‐world example based on French energy trading. We compare the value shown by our novel real‐world metric to traditional meteorological skill scores, and highlight key differences out beyond 2 weeks.